Development of STEM-Based Learning Tools to Increase Students' Mathematical Creative Thinking Ability through Inquiry Learning - Nurintya, Fairusz Hanan; Agoestanto, Arief (Department of Mathematics, Universitas Negeri Semarang, 2022)
This study aims to produce appropriate STEM nuanced learning tools on number material and find out the increase in students' mathematical creative thinking skills after the implementation of learning using STEM nuanced learning tools with inquiry learning models on number material. This study used the Research and Development (R&D) method. The R&D steps in this research are potential and problems, data collection, product design, product validation, testing, and the final product. The population in this study were students of class VII of SMP Negeri 8 Semarang, while the subjects in this study were students of class VII-F of SMP Negeri 8 Semarang, totaling 28 students. Data was collected using tests and questionnaires. The increase in mathematical creative thinking skills was analyzed using the N-Gain test from pretest and posttest data. The results showed that the learning tools with STEM nuances with the inquiry learning model developed had a decent level of feasibility, and there was an increase in students' mathematical creative thinking skills on each indicator after being given learning using STEM nuanced learning tools with inquiry learning models with moderate improvement criteria.